TANTANGAN INTEGRASI NILAI-NILAI PENDIDIKAN ISLAM DALAM PENDIDIKAN FORMAL - Rosmita Hapsun (Tazkiya: Jurnal Pendidikan Islam, 2025)
This study aims to examine the challenges of integrating Islamic educational values into formal education policies in Indonesia. The method used is a library research analysis of various scientific sources from 2019 to 2025. The results of the study indicate a disconnect between normative policies and implementation in the field, the dominance of cognitive aspects in the curriculum, and the limited capacity of teachers to integrate Islamic values effectively. Political dynamics and rapid regulatory changes also influence the direction and consistency of education policies. The lack of professional training, weak values-based evaluation, and a lack of structural support also hinder the integration process. This study concludes that strengthening the integration of Islamic values requires synergy between policymakers, educators, and the community. A contextual approach that is adaptive to local social and cultural conditions is also needed so that Islamic values can be instilled in a holistic, relevant, and sustainable manner within the formal education system. This can be an effective means of instilling Islamic values in a comprehensive and sustainable manner..